IMPLEMENTASI PROGRAM PEMIKAT J’TU (PENTAS MINAT BAKAT JUM’AT SABTU) DALAM PENGEMBANGAN KREATIVITAS SISWA DI SDN 44 KOTA BENGKULU - Afar Azis Rahman; Pebrian Tarmizi; Atika Susanti (Civic Society Research and Education: Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2025)
This study aims to describe the implementation of the Pemikat J'TU programme in developing student creativity through a descriptive qualitative approach. The research subjects consisted of the principal, chairman of the programme committee, teachers or trainers, and students. Data were collected through observation, interviews, and documentation, with analysis using the Miles and Huberman qualitative method which includes data collection, data reduction, data display, and conclusion drawing. The results showed that the J‘’TU Enchantment Programme is effective in encouraging student creativity through good coordination, motivation, and direction. Activities held every Friday and Saturday provide space for students to express themselves in art, religion, and literature. Creativity can be seen from the results of activities that reflect students' interests and talents, as well as the ability to think fluently, think flexibility, create and develop ideas. The success of the programme is supported by solid cooperation between teachers, students and parents, as well as motivation and feedback that boosts students' confidence.